2017
DOI: 10.1093/mnras/stx1653
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for measuring cosmic microwave background spectral distortions in the presence of foregrounds

Abstract: Measurements of cosmic microwave background spectral distortions have profound implications for our understanding of physical processes taking place over a vast window in cosmological history. Foreground contamination is unavoidable in such measurements and detailed signal-foreground separation will be necessary to extract cosmological science. In this paper, we present MCMC-based spectral distortion detection forecasts in the presence of Galactic and extragalactic foregrounds for a range of possible experimen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
146
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(158 citation statements)
references
References 101 publications
3
146
0
Order By: Relevance
“…Upcoming proposed CMB missions like PIXIE [42] would have an instrumental noise of nearly 3 − 4 orders of magnitude better than FIRAS and hence would be able to measure the CMB spectral distortions with an unprecedented accuracy [43]. Measurement of the spectral distortions signal will also depend upon the successful cleaning of the foreground contaminations [41,[44][45][46][47]. Other CMB missions like CORE [48] and LiteBIRD [49] would be able to measure the spatially fluctuating part of the spectral distortions [50] at a much better precision compared to Planck.…”
Section: Introductionmentioning
confidence: 99%
“…Upcoming proposed CMB missions like PIXIE [42] would have an instrumental noise of nearly 3 − 4 orders of magnitude better than FIRAS and hence would be able to measure the CMB spectral distortions with an unprecedented accuracy [43]. Measurement of the spectral distortions signal will also depend upon the successful cleaning of the foreground contaminations [41,[44][45][46][47]. Other CMB missions like CORE [48] and LiteBIRD [49] would be able to measure the spatially fluctuating part of the spectral distortions [50] at a much better precision compared to Planck.…”
Section: Introductionmentioning
confidence: 99%
“…Here we do not account for galactic foregrounds. In [38] it has been shown that the error on the measurement of the spectral distortion monopole can degrade as much as one order of magnitude with respect to earlier, more optimistic estimates. The spatially varying part of these foregrounds will have to be modelled with more accuracy in order to give an actual estimate of how much the estimates will degrade in our case.…”
Section: Y-distortion From Reionizationmentioning
confidence: 95%
“…Decays of the heavier states can also leave CMB spectral distortions detectable by the proposed PIXIE satellite [154][155][156][157]. Spectral distortions are a generic signal of sterile coannihilation, 1 For the DM mass chosen in the right panel of figure 13, DM annihilations into hadronic final states play an important role and are not treated by MicrOMEGASv4, which works in the partonic limit.…”
Section: Jhep08(2018)079mentioning
confidence: 99%
“…The bounds are discussed in the text and come from BaBar [150,151], E137 [152], LSND [153], BBN [77,78], and the CMB [154]. The reach for BDX and MiniBooNe adapted from [61], and PIXIE [154][155][156][157] (corresponding to µ < 5 × 10 −8 ) are shown. LDMX [158] can probe the entire allowed region of the left panel, but is not sensitive to the heavier dark photon mass on the right panel.…”
Section: ×10mentioning
confidence: 99%